Feasibility of Using Ionic Liquids as an Environment Friendly Corrosion Inhibitor of Carbon Steel in the Saline Solution - Manoharan, Avinash Kumar (IRC, 2016)
In this reportwork, the feasibility of using ionic liquids 1-ethyl-3-methylimidazolium tosylate, [EMIM][TOS], and 1-butyl-3-methylimidazolium tosylate, [BMIM][TOS] as inhibitor of carbon steel corrosion in saline solutions were investigated using weight loss and electrochemical methods. Carbon steel A760, which is widely used for piping in many industries such as water treatment and oil and gas platform was used as carbon steel sample. Seawater solution was taken from Pangkor Beach to mimic the real technical condition of saline solution in real practice. The methodology used in consisted of two major stages. First, in order to produce the desired ionic liquids, 1-ethyl-3-methylimidazolium chloride, [EMIm]Cl, and 1-butyl- 3-methylimidazolium chloride, [BMIm]Cl,were reacted with p-toulenesulfonic acid. The characterization of the synthesized ionic liquids was done using 1H and 13CNMR spectroscopies.